Teachers’ Satisfaction with Guidance Counseling Services in Elementary Schools - Lutfah, Ass.Lecture Nasser Thamer (Thi Qar Arts Journal, 2023)
The research that aims to identify the satisfaction of teachers with educational guidance services in primary schools. The sample of the research was 100 teachers, who were randomly selected. The researcher built the scale after reviewing previous studies and literature and presented it to a group of 6 experts in the field of psychological counseling and educational guidance. The alternatives followed in the answer were (completely satisfied, satisfied, neutral, dissatisfied, never satisfied). The reliability was obtained by the split-half method (0.925). The results showed that there was a statistically significant difference between the arithmetic mean and the hypothetical mean (60) in favor of the arithmetic mean (77.4000) for the scale of teacher satisfaction with guidance services. When comparing the calculated t-value (10.517) with the tabular t-value of (1.98) at a significance level of (0.05) with a degree of freedom (99).